Probiotic ice cream using buffalo milk dadih: Microbial, chemical, and sensory characteristics. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to find a quality probiotic ice cream formula by adding dadih, which is a result of the fermentation of buffalo milk in a bamboo tube. Materials and Methods: This study began with making dadih using 2 types of bamboo (Gigantochloa verticillata and Gigantochloa auriculata Kurz) to obtain dadih with the highest total probiotic colonies. Dadih with the highest colonies was used to continue the study. Furthermore, dadih was isolated to obtain the dominant lactic acid bacteria (LAB), which was identified molecularly using the 16S rRNA gene with the Polymerase polymerase chain reaction technique. The application of dadih into probiotic ice cream was conducted using a factorial completely randomized design with 2 factors. The first factor was the level of dadih, namely ICD 0 (ice cream without dadih), ICD 1 (5%), ICD 2 (10%), and ICD 3 (15%). The second factor was the length of ice cream storage (week), namely T0 (0), T1 (1), T2 (2) and T3 (3). Examination of pH, protein, fat content, and total bacterial colonies in ice cream was conducted. The research continued with sensory testing with 30 panelists. Results: The highest total probiotic colonies were 1 × 107 obtained in dadih fermented by Gigantochloa auriculata Kurz bamboo dominated by Weisselia paramesenteroides strain JCM 9890. pH of dadih was 4.52. Antimicrobial zones of dadih against Escherichia coli, Salmonella, and Staphylococcus aureus were 6.6, 8.1, and 7.7, respectively. The chemical quality test of ice cream showed that the pH was in the range of 6.21–5.61. Protein content ranged from 4.62 to 6.12, while fat content ranged from 6.03 to 8.12. Total ice cream colonies were in the range of 1 × 104 to 2.9 × 106. There was no interaction between the percentage of dadih and the length of ice cream storage time on the parameters of pH, protein, fat content, total LAB colonies, and sensory test result. The higher the dadih concentration, the more acidic the ice cream, and the higher the protein, fat content, and total LAB colonies. The sensory test showed that 15% of dadih was the most preferred by panelists. Conclusion: The conclusion of this study is that ice cream with a 15% dadih addition is the most preferred and proven probiotic ice cream.J. Adv. Vet. Anim. Res., 12(1): 214–221, March 2025http://doi.org/10.5455/javar.2025.l888